Anisotropic Bianchi type V perfect fluid cosmological models in Lyra's geometry - Ram S.; Zeyauddin M.; Singh C.P. (My University, 2025)
The law of variation for mean Hubble's parameter with average scale factor, in an anisotropic Bianchi type V cosmological space-time, is discussed within the frame work of Lyra's manifold. The variation of Hubble's parameter, which gives a constant value of deceleration parameter, generates two types of solutions for the average scale factor; one is the power-law and the other one is of exponential form. Using these two forms, new classes of exact solutions of the field equations have been found for a Bianchi type V space-time filled with perfect fluid in Lyra's geometry by considering a time-dependent displacement field. The physical and kinematical behaviors of the singular and non-singular models of the universe are examined. Exact expressions for look-back time, luminosity distance and event horizon versus redshift are also derived and their significance are discussed in detail. It has been observed that the solutions are compatible with the results of recent observations. © 2010 Elsevier B.V.